Proceedings of the III Advanced Ceramics and Applications Conference - Lee, William E.; Gadow, Rainer; Mitic, Vojislav; Obradovic, Nina (Atlantis Press : Imprint: Atlantis Press, 2016)
This is the Proceedings of III Advanced Ceramics and Applications conference, held in Belgrade, Serbia in 2014. It contains 25 papers on various subjects regarding preparation, characterization and application of advanced ceramic materials.